Introduction: Towards an Andean Ritology - Urbano, Henrique Osvaldo (1976)
In its almost ten years of existence, ALLPANCHIS PHUTURINQA devoted numerous ethnographic studies to Andean rites and rituals. Today he dedicates another edition to them in order to underline some ignored or less studied aspects of the issue. In this sense, the pages that we consecrate to the ethnohistory and to the survival of certain Inca rites beyond the movement of "extirpation of idolatry" should be read. In the same way, we want to insist on the urgent need to face the Andean reality starting from its own history and not only from some more or less abstract, more or less theoretical notion, however legitimate it may be. We cannot fully understand the Andean rites and rituals if we separate them from the global context where they were born, from the reasons that make them endure and even from the reasons that decreed their extinction.